Gifted students’ perceptions about intelligence: A metaphor study - Bilkay Bi; Seray Olçay (Elementary Education Online, 2023)
The purpose of this study is to investigate gifted students’ perceptions about intelligence. The study was conducted with a total of 103 students, 38 females and 65 males, attending a science and art center in Ankara. The data were collected through metaphors from the gifted students. The students were given a form prepared by the researchers, and they were asked to complete the form including the expression “Intelligence is like……. because……….”. As a result of the study, 68 valid metaphors related to the concept of intelligence were obtained. The metaphors produced were grouped under eight conceptual themes: “Changeable and Incremental, Tool functioning, Can be used for good or evil, Valuable, Associated with strong memory, Can be different from person to person, Unlimited, To be discovered” in terms of their common characteristics. As a result of the study, it is concluded that gifted students perceive intelligence at most as “money” and “galaxy” and generally have the perception of incremental intelligence.